Unexpected late-onset bleeding following thyroid surgery: case report and review of the literature - Marcianò, Marco; Vicari, Bianca; Orlando, Giuseppina; Melfa, Giuseppina; Campo, Isabella; Salamone, Giuseppe; Scerrino, Gregorio (Frontiers in Surgery, 2025)
Postoperative hematoma is an uncommon but potentially life-threatening and unpredictable complication of thyroid surgery. We report a case of very late postoperative bleeding occurring on the eighth postoperative day (POD) in a patient undergoing right lobe thyroidectomy who had restarted antiplatelet therapy since the first POD. The patient was readmitted to the emergency department with complaints of progressive anterior neck swelling and bleeding from the wound but without respiratory distress. Under general anesthesia, cervical reexploration allowed the detection of a hematoma situated in the right thyroid bed and subhyoid region and active bleeding of the superior thyroid vascular pedicle. Although most bleeding occurs within 24 h, caution should be taken in patients who are in need of antiplatelet therapy, and close monitoring should also be advised at home after discharge.